Small Heat Shock Proteins, Big Impact on Protein Aggregation in Neurodegenerative Disease - Webster, Jack M.; Darling, April L.; Uversky, Vladimir N.; Blair, Laura J. (Frontiers in Pharmacology, 2019)
Misfolding, aggregation, and aberrant accumulation of proteins are central components in the progression of neurodegenerative disease. Cellular molecular chaperone systems modulate proteostasis, and, therefore, are primed to influence aberrant protein-induced neurotoxicity and disease progression. Molecular chaperones have a wide range of functions from facilitating proper nascent folding and refolding to degradation or sequestration of misfolded substrates. In disease states, molecular chaperones can display protective or aberrant effects, including the promotion and stabilization of toxic protein aggregates. This seems to be dependent on the aggregating protein and discrete chaperone interaction. Small heat shock proteins (sHsps) are a class of molecular chaperones that typically associate early with misfolded proteins. These interactions hold proteins in a reversible state that helps facilitate refolding or degradation by other chaperones and co-factors. These sHsp interactions require dynamic oligomerization state changes in response to diverse cellular triggers and, unlike later steps in the chaperone cascade of events, are ATP-independent. Here, we review evidence for modulation of neurodegenerative disease-relevant protein aggregation by sHsps. This includes data supporting direct physical interactions and potential roles of sHsps in the stewardship of pathological protein aggregates in brain. A greater understanding of the mechanisms of sHsp chaperone activity may help in the development of novel therapeutic strategies to modulate the aggregation of pathological, amyloidogenic proteins. sHsps-targeting strategies including modulators of expression or post-translational modification of endogenous sHsps, small molecules targeted to sHsp domains, and delivery of engineered molecular chaperones, are also discussed.